Project: "Scaling up Soil Carbon Enhancement for Food Security and Climate Across Complex Landscapes in Kenya and Ethiopia": Dissemination Workshop presentations. - Girvetz, Evan Hartunian; Nyawira, Sylvia; Chere, Zerihun; Abegaz, Assefa; Jebet, Mercy; Pikki, Kristin; Söderström, Mats; Abera, Wuletawu; Munyialo, Susan; Magambo, George; Ma, Jianyong; Karanja Ng'ang'a, Stanley (2020)
These presentations provide an overview of the key research outcomes from the BMZ-funded project on Scaling up Soil Carbon Enhancement for Food Security Across Complex Landscapes in Kenya and Ethiopia. These project results were presented during the final virtual dissemination workshop for the project held on 10th and 11th December 2020. The project has been running for 4 years (Jan 2017 to Dec 2020). The project was led by the Alliance of Bioversity International and CIAT with partners from the Karlsruhe Institute of Science and Technology (KIT) , Swedish University of Agricultural Sciences (SLU), Addis Ababa University, University of Nairobi, Ethiopian Institute of Agricultural Research (EIAR) and Kenya Agricultural Livestock and Research Organization (KALRO).